Cohort study evaluating the risk of hip fracture among patients with dementia in Taiwan. (28th October 2014) - Huang, Shih‐Wei; Lin, Jia‐Wei; Liou, Tsan‐Hon; Lin, Hui‐Wen
<x xml:space="preserve">Abstract</x> Background To investigate the incidence and risk of hip fracture among dementia patients Methods This is a retrospective population‐based 7‐year cohort study using case–control matched analysis database from Taiwan's Longitudinal Health Insurance Database 2005. Patients were diagnosed with codes or International Classification of Diseases‐9‐CM codes of dementia, between 1 January 2004 and 31 December 2006. The prevalence and the adjusted odds ratio of hip fracture among dementia patients and the controls were estimated. Results We enrolled 3101 patients with dementia in the dementia cohort and 12, 404 (1:4) patients in the control group. Of these, 202 patients experienced hip fractures. The incidence of hip fracture was 1178 per 100, 000 person‐years in the dementia cohort and 624 per 100, 000 person‐years in the comparison cohort. The hip fracture hazard ratio during the follow‐up period was 1.89 (95% confidence interval [CI] 1.60–2.23, p < 0.001) for dementia patients. After adjusting for the covariates, the hazard ratio of hip fracture was 1.41 (95% CI, 1.19–1.69, p < 0.001) for dementia patients. Conclusion People with dementia experience an increased incidence of hip fracture and are at a higher risk of sustaining a hip fracture in the future. Proper and effective hip fracture‐prevention strategies are essential for dementia patients. Copyright © 2014 John Wiley & Sons, Ltd.